Collective action in community management of grazing lands: the case of the highlands of northern Ethiopia - Benin, Samuel; Pender, John L. (Cambridge University Press, 2006)
Collective action can play a significant role in sustainable management of common grazing lands through restricting access and regulating use. However, it is not clear why there are often violations of grazing restrictions in equilibrium. This paper first presents a theoretical framework of collective action in community management of grazing lands that explicitly models individual violations behaviour. Then data from the highlands of Amhara region of Ethiopia are used to test the model predictions to examine the impact of policy-relevant factors on collective establishment of grazing restrictions and violations of grazing restrictions. Econometric results show that collective action in community grazing land management is likely to be more beneficial and effective in communities with better market access or higher populations. Collective action, on the other hand, is less likely to be successful in communities with greater social, economic, or cultural heterogeneity or more affluent members. Factors related to greater livestock profitability, such as rainfall, or fixed costs of negotiating agreements, such as total land area of the community, have ambiguous effects, as they are associated with establishment of grazing restrictions as well as violating the restrictions.